2007
DOI: 10.1080/10428190701344881
|View full text |Cite
|
Sign up to set email alerts
|

CHOP-R therapy overcomes the adverse prognostic influence of BCL-2 expression in diffuse large B-cell lymphoma

Abstract: BCL-2 protein expression correlates with shorter survival in patients with diffuse large B cell lymphoma (DLBCL) who are treated with CHOP chemotherapy. We report a retrospective analysis of the prognostic significance of BCL-2 status in patients who received CHOP with the addition of rituximab (CHOP-R) for DLBCL. Patients over 15 years of age with de novo, HIV negative DLBCL, without CNS involvement, and known BCL-2 protein status were identified from the BCCA Lymphoid Cancer Database. BCL-2 tumour positivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
4
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 29 publications
5
28
4
5
Order By: Relevance
“…Several recent studies of R-CHOP cohorts have failed to show a BCL2 prognostic effect due to a disproportionate benefit from rituximab of BCL2-positive cases and with no association of BCL2 expression with OS in DLBCL (23)(24)(25). Similarly, a patient cohort treated with rituximab and EPOCH also showed no association of BCL2 with OS or EFS (41).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several recent studies of R-CHOP cohorts have failed to show a BCL2 prognostic effect due to a disproportionate benefit from rituximab of BCL2-positive cases and with no association of BCL2 expression with OS in DLBCL (23)(24)(25). Similarly, a patient cohort treated with rituximab and EPOCH also showed no association of BCL2 with OS or EFS (41).…”
Section: Discussionmentioning
confidence: 95%
“…Because the standard treatment of DLBCL now includes rituximab, several studies with conflicting observations concerning prognostic value of BCL2 expression in R-CHOP-treated patients have been reported in recent years with some showing (22,23) and some not (24,25) showing any prognostic significance. Therefore, we analyzed our cohort of GEP-defined DLBCL to determine whether BCL2 overexpression still has prognostic value in patients with DLBCL treated in the R-CHOP era.…”
Section: Introductionmentioning
confidence: 99%
“…21,23,24,[37][38][39][40][41][42][43][44] Most of these studies had small patient cohorts and/or also did not address the confounding effects of other factors, such as MYC expression. In this study, we found that BCL2 expression predicted survival in DLBCL in the overall patient cohort and in the COO subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…26 The prognostic significance of Bcl-2 expression is also controversial, and comparison between different studies is hampered by the choice of different cut-offs of positive cells, and by the variability of treatments. In patients treated with R-CHOP, Bcl-2 protein did not correlate with outcome, 5,27 since the addition of rituximab seemed to improve survival of Bcl-2-positive patients, [28][29][30] apparently eliminating the gap between Bcl-2-positive and Bcl-2-negative patients found in the pre-rituximab era. This result does, however, appear to be contradicted in a very recent study in which Bcl-2 expression in GCB-DLBCL was associated with poorer outcome.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%